Pemanfaatan Rempah Dapur sebagai Minuman Herbal untuk Penyembuhan Berbagai Penyakit di Desa Cimalaka, Sumedang Jawa Barat - Fida Qurrotul Aini; Tri Cahyanto (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2024)
Spices are parts of plants such as leaves, stems, rhizomes, seeds and other parts. One product made from spices is a functional drink. This functional drink has many good benefits for the body, including preventing various diseases, preventing the aging process, and maintaining the body's immune system. Herbal drinks are a functional drink that has many benefits for the body, the basic ingredients for which are made using spices that are often found around. People in Cimalaka Village are used to using kitchen spices to make herbal drinks. The aim of this research is to determine the benefits of kitchen spices used by the people of Cimalaka Village as ingredients for making herbal drinks which are commonly consumed by the people in the village. The research was conducted in September-November 2024. The method used in this research used a quantitative approach with the measurement parameters Use Value (UV) and Informant Consensus Factor (ICF). This sample was taken using the snawball sampling technique with a total of 31 respondents. The research results showed that the highest spice utilization value was lemongrass (UV = 0.61) with a UV percentage of 22%, and the lowest spice utilization value was garlic (UV = 0.16) with a UV percentage of 6%. With the highest ICF value of 1, namely rheumatism, gout and gastritis with a percentage value for each disease of 21%. And the disease with the lowest uniformity value, the ICF value is 0.86, namely cholesterol disease with a percentage value of 18%. Herbal drinks have benefits for the people of Cimalaka Village which can be seen from the diversity of benefits.